2021
DOI: 10.21037/tau-20-1114
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the association between serum uric acid and testosterone in adult males: NHANES 2011–2016

Abstract: Background: Previous studies have suggested that the possible relationship between serum uric acid (SUA) and testosterone. However, the results of previous studies are controversial and there is limited evidence examining the relationship between SUA and testosterone in a general US population of men. The objective of this study is to explore the correlation of SUA and testosterone among adult males from the US.Methods: Data from the National Health and Nutrition Examination Survey 2011-2016 were used, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Likewise, estradiol (E2) is negatively correlated with female uric acid and positively correlated with male uric acid. Other researchers have found that the relationship is no longer significant among postmenopausal women and men over 65, and the mechanism was still unclear ( 14 , 15 ). At present, there is no objective report on the dose-response relationship between sex hormones and HUA.…”
Section: Introductionmentioning
confidence: 98%
“…Likewise, estradiol (E2) is negatively correlated with female uric acid and positively correlated with male uric acid. Other researchers have found that the relationship is no longer significant among postmenopausal women and men over 65, and the mechanism was still unclear ( 14 , 15 ). At present, there is no objective report on the dose-response relationship between sex hormones and HUA.…”
Section: Introductionmentioning
confidence: 98%
“…The SU levels in our study were similar to those found in a nutritional and health survey conducted in Taiwan from 1993 to 1996, which showed that the mean SU level in males was 6.63 mg/dL [ 4 ]. Several studies have assessed the relationship between the total testosterone and SU levels [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 20 , 34 ]. Han et al [ 20 ] conducted a study among 7796 patients in China from 2011 to 2016 and showed that the SU levels were negatively associated with total testosterone level in adult males.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have assessed the relationship between the total testosterone and SU levels [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 20 , 34 ]. Han et al [ 20 ] conducted a study among 7796 patients in China from 2011 to 2016 and showed that the SU levels were negatively associated with total testosterone level in adult males. The mean age of their study participants was 47.6 years, and the mean total testosterone level was 417 ng/dL, which are similar to those in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum UA levels have been reported to be negatively correlated with testosterone levels (21). Testosterone affects the expression pattern of urate transporters in the kidneys, such as urate transporter 1, glucose transporter 9, and sodium-coupled monocarboxylate transporter 1, which induces UA reabsorption in males (22).…”
Section: Discussionmentioning
confidence: 99%